The Effectiveness of Lateral Hop and Leg Press Training on Limb Strength and Explosive Power for Athletes - Nurrochmah, Siti (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2022)
The aim of the study was to examine the effectiveness of fast lateral hop (LHC), slow lateral hop (LHL) and leg press (LLP) training on increasing the strength and explosive power of the leg muscles simultaneously. The approach method is in the form of an experiment using a Randomized Pretest-Posttest Control Group Design. The sample is 51 people divided into three groups using the ordinal pairing matched technique. Data were obtained using test and non-test instruments and collected using experimental techniques, observation and physical condition tests. Data analysis using one-way Manova technique Hotelings Trace method. The results of the analysis found that the F test = 25,413 and the significance of F = 0.000 < 0.05, meaning that LHC, LHL and LLP training were effective in increasing the strength and explosive power of the leg muscles simultaneously. The results of the Between-Subjects Effects analysis in the form of partial eta squared variation KOT 15.6% and variation DEOT = 63.4%. The conclusion of the study was that there was a significant effect of LHC, LHL and LLP training on increasing the strength and explosive power of the leg muscles simultaneously. LLP training is more effective in increasing leg muscle strength, and LHC training is more effective in increasing the power of leg muscles.